Clinical, cytologic, bacteriologic and radiographic analysis of respiratory diseases in dogs - Mehmet Maden; Fatih M. Birdane; Fahrettin Atkan; Hasan H; Hadimli (Eurasian Journal of Veterinary Sciences)
Clinical, cytological, bacteriological and radiographic analysis of respiratory tract diseases were performed in dogs. The importance of bronchoalveolar lavage (BAL) (Kid and culture were analysed and it is considered to be important to detect the ethiologic factor and overall rate of inflammation. In addition to this, radiography were also evaluated if there was any contribution to the diagnosis. Thirty one dogs were used in this study, of which 6 was assigned as a control group. Cough, fever, nasal discharge and abnormal auscultation were found in trac-heabronchitis and bronchopneumonia. While there was a statistically significant increase (p<0,0011 in the neutrophil counts, there was a statistically significant decrease (p<0.001) on macrophage and lenfocyte counts in both groups Statistically sıgnilıcani increase (p<0.05) on epithel cells counts was found Coc and/or bacits were seen in all cases Three dogs had fungal organisms, and one had anaerob bacteria Uordetella bronchiseptica and E coli (% 24) were the most isolated bacteria species in BAL fluid culture. Tracheabronchitis and bronchopneumonia findings were determined radiographically As a result, clinical, cytologic, bacteriolcgic and radiographic findings were considered to be important in the diagnosis of respiratory diseases Especially. BAL fluid cytology was found to be highly important tool in the diagnosis.